Penyuluhan Stunting dan Upaya Pencegahannya Kepada Masyarakat Teluk Pakedai Kab. Kuburaya - Titin, Titin; Wahyuni, Eko Sri; Putri, Ruqiah Ganda; Candramila, Wolly; Yeni, Laili Fitri; Nurdini, Asriah; Daningsih, Entin; Syamswisna, Syamswisna (Jurnal ABM Mengabdi, 2024)
Stunting is a health problem toddler in the form of failure to thrive due to inadequate nutritional intake, causing short stature to be inappropriate for their age. Based on data collected by the West Kalimantan Provincial Health Office, the prevalence of stunting under five in 2021 in West Kalimantan will reach 17.75%. The area of Selat Remis Village, Teluk Pakedai District, Kubu Raya Regency, West Kalimantan, is still facing stunting problems due to the lack of awareness and knowledge of the population regarding the importance of a balanced nutritional intake. The prevalence of stunting under five is based on data collected by the West Kalimantan Health Service in 2021, as many as 7.87% or a total of 2,554 under five are stunted in Kubu Raya Regency (West Kalimantan Provincial Health Office, 2021). The PKM activity was carried out in the Selat Remis Village Office Hall which was attended by 27 participants consisting of local residents and students of Biology Education FKIP Tanjungpura University. Activities consisted of delivering material, question and answer, filling out response questionnaires and distributing prizes. More than 90% of the participants who attended stated that the counseling activities carried out provided benefits related to stunting information.